LAJU GALAT BIT AKIBAT KESALAHAN PENGARAHAN ANTENA STASIUN BUMI KE SATELIT - Wahyu Pamungkas; Anggun Fitrian Isnawati (Universitas Ahmad Dahlan, 2010)
One problem causing reduction of energy in satellite communications system is the misalignment of earth station antenna pointing to satellite. Error in pointing would affect the quality of information signal to energy bit in earth station. In this research, error in pointing angle occured only at receiver (Rx) antenna, while the transmitter (Tx) antennas precisely point to satellite. The research was conducted towards two satelites, namely TELKOM-1 and TELKOM-2. At first, measurement was made by directing Tx antenna precisely to satellite, resulting in an antenna pattern shown by spectrum analyzer. The output from spectrum analyzers is drawed with the right scale to describe swift of azimuth and elevation pointing angle towards satellite. Due to drifting from the precise pointing, it influenced the received link budget indicated by pattern antenna. This antenna pattern shows reduction of power level received as a result of pointing misalignment. As a conclusion, the increasing misalignment of pointing to satellite would affect in the reduction of received signal parameters link budget of downlink traffic.